Ambush by Dre : the National Football League and the challenges arising from conflicting sponsorship strategies - Naraine, Michael L.; S?guin, Benoit, 1966-; MacIntosh, Eric W., 1977- (London : Human Kinetics, Inc., 2015)
In this case study, students are exposed to the issue of stakeholder management through the lens of the National Football League (NFL), using a contemporary example of ambush marketing and player endorsement deals as the primary context. The case depicts nonfictitious events that involve players and their disdain for league policies regarding donning brands and products that violate exclusivity agreements the league has with other companies. After identifying the origins of the circumstances, the case profiles the three principal stakeholder groups involved (i.e., the players, the ambushed sponsor, and the focal organization) through their respective leaders (i.e., DeMaurice Smith, executive director of the NFL players association, Bob Maresca, president of Bose Corporation, and Roger Goodell, Commissioner of the NFL). Using fictitious commentary, the case culminates with the three actors utilizing the services of a sports consultancy firm as they work together to determine the best course of action. Learning objectives include understanding collegiality in a professional setting, and mitigating conflicting sponsorship strategies.
Originally published in Naraine, M. L., Seguin, B., & MacIntosh, E. (2015). Ambush by Dre: The National Football League and the challenges arising from conflicting Sponsorship Strategies. Case Studies in Sport Management, 4(1), 147-154. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; National Football League -- Case studies; Social responsibility of business; Football -- Economic aspects -- United States -- Case studies; Social responsibility of business -- United States -- Case studies; Sports sponsorship -- United States -- Case studies